The Microeconomics of Creating Productive Jobs : A Synthesis of Firm-Level Studies in Transition Economies - Brown, J. David; Earle, John S. (World Bank, Washington, DC, 2012)
The challenge for labor market policy in the transition economies has been to redress the sharp drops in employment and rises in unemployment in a way that fosters the creation of productive jobs. The authors first document the magnitude and productivity of job and worker reallocation. Then they investigate the effects of privatization, product and labor market liberalization, and obstacles to growth in the new private sector on reallocation and its productivity in Hungary, Romania, Russia, and Ukraine. The authors find that market reform has resulted in a large increase in the pace of job reallocation, particularly that occurring between sectors and through firm turnover. Unlike under central planning, the job reallocation during the transition has contributed significantly to aggregate productivity growth. Privatization has not only stimulated intrasectoral job reallocation, but the reallocation is more productive than that among remaining state firms. The effect of privatization on firm productivity varies considerably across countries and is not always positive. The productivity gains from privatization have generally not come at the expense of workers but are rather associated with increased wages and employment.